2013
DOI: 10.1371/journal.pone.0068197
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic Acid Induces Osteoblastic Differentiation in Vascular Smooth Muscle Cells through ACSL3 and NF-κB, Novel Targets of Eicosapentaenoic Acid

Abstract: Free fatty acids (FFAs), elevated in metabolic syndrome and diabetes, play a crucial role in the development of atherosclerotic cardiovascular disease, and eicosapentaenoic acid (EPA) counteracts many aspects of FFA-induced vascular pathology. Although vascular calcification is invariably associated with atherosclerosis, the mechanisms involved are not completely elucidated. In this study, we tested the hypothesis that EPA prevents the osteoblastic differentiation and mineralization of vascular smooth muscle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 39 publications
2
41
1
Order By: Relevance
“…Triacsin C is known to inhibit ACSL1, 3, and 4 activation 26) . In macrophages and vascular smooth muscle cells, the expression of at least ACSL1, 3, and 4 has been confirmed, and it is known that PA induces ACSL expression in these cells 11,12) . In this study, we demonstrated that PA augmented the expression of ACSL isoforms in vascular endothelial cells as well, in particular ACSL3, while EPA inhibited the increase in their expressions (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Triacsin C is known to inhibit ACSL1, 3, and 4 activation 26) . In macrophages and vascular smooth muscle cells, the expression of at least ACSL1, 3, and 4 has been confirmed, and it is known that PA induces ACSL expression in these cells 11,12) . In this study, we demonstrated that PA augmented the expression of ACSL isoforms in vascular endothelial cells as well, in particular ACSL3, while EPA inhibited the increase in their expressions (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…In particular, an excess of saturated fatty acids is considered a risk factor for cardiovascular disease and has been reported to trigger inflammatory signals in various tissues and promote lipotoxicity 10) . In order to elucidate the mechanism of the anti-atherogenic effect of EPA, we studied lipotoxicity in vascular cells and showed that palmitic acid (PA), a major saturated fatty acid in plasma, stimulates inflammatory cytokine production in macrophages as well as osteoblastic differentiation of vascular smooth muscle cells, and that this action could be mediated by long-chain acyl-CoA synthetase (ACSL), an enzyme that converts free fatty acids into acyl-CoA derivatives 11,12) . Furthermore, we also reported that EPA may ameliorate lipotoxicity in macrophages and vascular smooth muscle cells through the common mechanism of ACSL expression regulation.…”
Section: Elisamentioning
confidence: 99%
“…However, there is no effective therapy currently available. We and other groups recently demonstrated that the accumulation of SFAs through either SCD inhibition or exogenous supplementation potently induces mineralization and osteogenic differentiation of VSMCs (15,47). However, whether SCD inhibition and SFA accumulation causes vascular calcification in vivo was not determined.…”
Section: Discussionmentioning
confidence: 96%
“…Several in vitro and in vivo studies have shown lipids to play a causative role in the pathogenesis of vascular calcification in addition to inorganic phosphate, inflammatory cytokines, and oxidative stress (6)(7)(8)(9)(10)(11)(12)(13). Treatment with unsaturated fatty acids (UFAs) inhibits vascular mineralization and osteogenic differentiation (14,15), whereas oxidized lipids, such as oxysterols and oxidized phospholipids, elicit procalcific effects in vascular cells (9,16,17). In addition to this evidence, we also previously reported that saturated fatty acids (SFAs) and calcium simultaneously accumulate during osteogenic differentiation of vascular cells (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, some studies have shown that EPA has the capability to directly and indirectly activate the nuclear factor kappa B (NF-κB) pathway (Kageyama et al 2013;Zuniga et al 2011), and this pathway is responsible for the control of the gene expression of several anti-oxidant enzymes, including CAT (Priyanka et al 2013). Thus, the modulation of NF-κB pathway by EPA may modulate the CAT content, and consequently, its activity, furthermore, allosteric mechanisms, can modulate the enzyme activity as demonstrated above.…”
Section: Discussionmentioning
confidence: 95%